Is there enough water in the Vientiane Plain? a water balance assessment of the Lower Nam Ngum Basin. Project report prepared by IWMI for CSIRO - AusAID Research for Development Alliance under the project "Exploring Mekong Region Futures". - Lacombe, Guillaume; Douangsavanh, Somphasith; Thepphavong, B.; Hoanh, Chu Thai; Bounvilay, B.; Noble, A.D.; Ongkeo, O.; Johnston, Robyn M.; Phongpachith, C. (International Water Management Institute, 2011)
In Lao PDR, one of the less developed countries, water represents a valuable natural resource via the development of hydropower dams and irrigation schemes. In the lower part of the Nam Ngum River Basin, the Vientiane plain is one of the largest food production areas of the country and the largest irrigated area in Lao PDR. While food demand is expected to continue to increase in the future, hydropower dams are under rapid development in the upper part of the basin, modifying the seasonal distribution of the river flow regimes. This study aims at assessing the current water supply and agricultural water demand in the Vientiane Plain and concluding whether the water resource is or may become a limiting factor for food production. The agricultural water demand is assessed from two types of data (characteristics of large-scale pumping stations and official statistics on irrigated areas) and using remote sensing analyses. Flow measurements of the Nam Ngum River were used to quantify the water supply. A 43-year time series (1962-2004) of daily river discharge was reconstructed from actual discontinuous data recorded in the river reach where most of the pumping stations are found. Distinctions in the water resource assessment were made between pristine conditions (before the construction of the hydropower dams) and current conditions of water infrastructure development. A comparison of the water supply and demand indicates that during the 4 driest months of the year (January to April) when the river reaches its minimum level and the irrigation water demand is the highest, pumped volumes represent less than 30% of the river discharge. This ratio should decrease as new hydropower dams are built, storing and releasing more water during the wet and the dry season, respectively. These figures indicate that the availability of water in the Nam Ngum River is not a limiting factor for irrigation, even during the dry seasons of exceptionally dry years. The water demand could exceptionally exceed the water supply in the case of an extreme scenario of irrigation development with irrigated areas 3-fold larger than the current ones. Next analyses will consist in assessing how this water balance will be altered by the development of new hydropower dams and irrigation projects. Possible uses of water surplus will be prioritized, depending on their economic viability and benefits.